Case report: Left bundle branch pacing guided by real-time monitoring of current of injury and electrocardiography - Shen, Jiabo; Jiang, Longfu; Wu, Hao; Li, Hengdong; Zhong, Jinyan; Pan, Lifang (Frontiers in Cardiovascular Medicine, 2022)
Background Left bundle branch (LBB) pacing (LBBP) has recently emerged as a physiological pacing mode. Current of injury (COI) can be used as the basis for electrode fixation position and detection of perforation. However, because the intermittent pacing method cannot monitor the changes in COI in real time, it cannot obtain information about the entire COI change process during implantation. Case summary Left bundle branch pacing was achieved for treatment of atrioventricular block in a 76-year-old female. Uninterrupted electrocardiogram and electrogram were recorded on an electrophysiology system. In contrast to the interrupted pacing method, this continuous pacing and recording technique enables real-time monitoring of the change in ventricular COI and the paced QRS complex as the lead advances into the interventricular septum. During the entire screw-in process, the COI amplitude increased and then decreased gradually after reaching the peak, followed by a small but significant, rather than dramatic, decrease. Conclusion This case report aims to demonstrate the clinical significance of changes in COI and QRS morphology for LBBP using real-time electrocardiographic monitoring and filtered and unfiltered electrograms when the lead is deployed using a continuous pacing technique. The technique could be used to confirm LBB capture and avoid perforation.